Growth effects of N-acylethanolamines on gut bacteria reflect altered bacterial abundances in Inflammatory Bowel Disease - Fornelos, Nadine (Nat Microbiol, 2020)
Inflammatory bowel diseases (IBD) are associated with alterations in gut microbial abundances and lumenal metabolite concentrations, but the effects of specific metabolites on the gut microbiota in health and disease remain largely unknown. Here, we analyzed the influences of metabolites that are differentially abundant in IBD on the growth and physiology of gut bacteria that are also differentially abundant in IBD. We found that N-acylethanolamines (NAEs), a class of endogenously-produced signaling lipids elevated in the stool of IBD patients and a T-cell transfer model of colitis, stimulated growth of species overrepresented in IBD and inhibited that of species depleted in IBD in vitro. Using metagenomic sequencing, we recapitulated the effects of NAEs in complex microbial communities ex vivo, with Proteobacteria blooming and Bacteroidetes declining in the presence of NAEs. Metatranscriptomic analysis of the same communities identified components of the respiratory chain as important for the metabolism of NAEs, and this was verified using a mutant deficient for respiratory complex I. In this study, we identified NAEs as a class of metabolites that are elevated in IBD and have the potential to shift gut microbiota toward an IBD-like composition.